Impacto de las actividades productivas en el desarrollo socioeconómico de los habitantes de la parroquia Uzhcurrumi año 2021 - Briones Armijos, Bangelle Carolina; Maldonado Procel, Juleysi Estefanía (Machala, 2021)
This research study entitled "Impact of productive activities on the socioeconomic development of the inhabitants of the Uzhcurrumi Parish. Year 2021", arises as a concern of its authors after knowing certain baseline information that allowed inferring the existence of an economic and social problem with serious consequences in the socio-family development of the population of this important locality. The problem referred to is associated with the productive decline of traditional primary activities, socioeconomic poverty and the exodus of young people who migrate to other cities in search of opportunities. The rural parish of Uzhcurrumi, which belongs to the Pasaje Canton of the province of El Oro, has a history that testifies to having been a place of abundant agricultural and livestock production and commercialization that satisfied the demand for food products from the Ecuadorian Austro and from the lower and upper parts of the province based on productive exchange. Currently the population continues to dedicate itself mainly to the legendary agricultural and livestock production keeping alive the history and tradition, however, the lack of self-management and government support have determined a sense of productive decline, and with it, the deterioration of local socioeconomic development. Several causal factors converge in the explanation of this problematic reality, but without a doubt, it is focused on the absence of local planning oriented to productive diversification, even more so, if we consider the great potential for socioeconomic development that the territory possesses. The lack of management in this sense has led to the degradation of traditional productive activities, the reproduction of socioeconomic poverty and the migration of youth to other cities in the province and the country, a fact that allows us to glimpse a critical trend horizon in the immediate future of the Parish. The main objective of the research was to determine the level of impact generated by productive activities on the socioeconomic development of the Uzhcurrumi parish of the Pasaje canton. The study assumes the characteristics of a descriptive and explanatory diagnostic research, with a theoretical foundation in the empirical-inductive epistemological approach and philosophical support in logical positivism. Consequently, the quantitative methodological approach was adopted, with the use of techniques and instruments such as structured observation, questionnaire and semi-structured interview, which made possible the apprehension of important empirical information. The results of the diagnostic research verified the existence of a limited contribution of traditional productive activities to local socioeconomic development, with full identification of the causal system of the fact, especially the limited management and planned intervention of the local GAD in the design of a productive diversification plan, the weak cohesion, organization and social participation in the analysis and solution of community problems. This situation has caused small farmers to generate only a captive economy, i.e., production for self-consumption and survival of the local inhabitants. Finally, the systematized empirical information would give rise to the construction of a matrix of community requirements, from whose justifying analysis of relevance, operational feasibility and social impact, the most appropriate requirement was selected, which would give rise to the intervention proposal consisting of the planning of a Training Program for the development of community micro-entrepreneurship, as a strategy for local productive diversification, all oriented to the expansion of the productive offer, the reduction of poverty, to stop the exodus of young people, the improvement of the quality of life and the good family and social life.
El presente estudio investigativo intitulado “Impacto de las actividades productivas en el desarrollo socioeconómico de los habitantes de la Parroquia Uzhcurrumi. Año 2021”, surge como una inquietud de sus autoras al conocer cierta información de línea base que permitía inferir la existencia de una problemática económica y social con graves secuelas en el desarrollo sociofamiliar de la población de esta importante localidad. EL problema al que se hace referencia está asociado al decaimiento productivo de las actividades primarias tradicionales, a la pobreza socioeconómica y al éxodo de los jóvenes quienes emigran a otras ciudades en busca de oportunidades. La parroquia rural Uzhcurrumi que pertenece al Cantón Pasaje de la provincia de El Oro, registra una historia que testimonia haber sido un sitio de abundante producción y comercialización agrícola y ganadera que satisfacía la demanda de productos alimenticios del austro ecuatoriano y de las partes baja y alta de la provincia en base al intercambio productivo. Actualmente la población sigue dedicándose mayoritariamente a la legendaria producción agrícola y pecuaria manteniendo viva la historia y tradición, sin embargo, la falta de autogestión y apoyo gubernamental han determinado un sentido decrecimiento productivo, y con ello, el deterioro del desarrollo socioeconómico local. En la explicación de esta realidad problémica convergen varios factores causales, pero sin lugar a dudas, este se focaliza en la ausencia de la planificación local orientada a la diversificación productiva, más aún, si de consideran las grandes potencialidades para el desarrollo socioeconómico que posee el territorio. La falta de gestión en ese sentido ha conllevado a la degradación de las actividades productivas tradicionales, a la reproducción de la pobreza socioeconómica y a la migración de la juventud hacia otras ciudades de la provincia y del país, hecho que permite vislumbrar un horizonte tendencial critico en el futuro inmediato de la Parroquia. El objetivo central de la investigación estuvo direccionado a determinar el nivel de impacto que generan las actividades productivas en el desarrollo socioeconómico de la parroquia Uzhcurrumi del cantón Pasaje. El estudio asume características de una investigación diagnóstica descriptiva y explicativa, con fundamento teórico en el enfoque epistemológico empírico-inductivo y con sustento filosófico en el positivismo lógico. Consecuentemente se abrazó el enfoque metodológico cuantitativo, con uso de técnicas e instrumentos tales como la observación estructurada, el cuestionario y la entrevista semiestructurada, que posibilitaron la aprehensión de importante información empírica. Los resultados de la investigación diagnóstica permitieron verificar la existencia de una limitada contribución de las actividades productivas tradicionales al desarrollo socioeconómico local, con plena identificación del sistema de causal del hecho, en especial, la limitada gestión e intervención planificada del GAD local en el diseño de un plan de diversificación productiva, la débil cohesión, organización y participación social en el análisis y solución de los problemas comunitarios. Esta situación ha provocado que los pequeños productores agropecuarios solo generen una economía cautiva, es decir, producción para el autoconsumo y sobrevivencia de los habitantes del lugar. Finalmente, la información empírica sistematizada, daría lugar a la construcción de una matriz de requerimientos comunitarios, de cuyo análisis justificativo de pertinencia, viabilidad operativa e impacto social, se seleccionó el requerimiento más apropiado, mismo que daría lugar a la propuesta interventiva consistente en la planificación de un Programa de Capacitación para el desarrollo del emprendimiento microempresarial comunitario, como estrategia de diversificación productiva local, todo ello orientado a la ampliación de la oferta productiva, a la reducción de la pobreza, a detener el éxodo de los jóvenes, al mejoramiento de la calidad de vida y al buen vivir familiar y social.
Keywords: ACTIVIDAD PRODUCTIVA; UZHCURRUMI; DESARROLLO; ECONOMIA